Uma tentativa de caracterização da prática clínica do analista do comportamento no atendimento de clientes com e sem o diagnóstico de transtorno-obsessivo-compulsivo - Zamignani, Denis Roberto (2001)
The psychiatry manuais, in the case of OCD, assign to a private event - obsession - the status of the initiating cause of the compulsive behavior, and the specialized literature suggests procedures that are based upon the topography of the responses involved in OCD. An approach based on behavior analysis, on the other hand, emphasizes the need for a functional analysis of the relationships between a client's responses and environmental consequences. These two distinct explanatory models may bring about difficulties for the behavior analyst dealing with psychiatric patients. This work aimed at characterizing the behavior analyst performance in a therapeutic setting with clients with or without a diagnosis of Obsessive-Compulsive Disorder (OCD) Method: The verbal interactions of two therapists identified as behavior analysts - each one with one client with and one client without an OCD diagnosis - were compared. Four to tive sessions of each pair (therapist - client) were recorded. The therapist and clients' verbalizations were classified according to their relation to the client's complaint, and were categorized as: questions, descriptions, explanations, advices, feedback, inferences or other. Therapist's verbalizations that immediately followed client's verbalizations related or not to complaint were analyzed. Therapist' s verbalizations classified as explanations and advices were also analyzed in arder to verify their consistency with the radical behaviorist approach. Results: Results indicated differences between the two therapists: the first therapist had a high percentage of her verbalization categorized as feedback while the other therapist had a high percentage of verbalizations classified as giving advice and explaining. For both therapists, the majority of their explanations were classified as having emphasizing the response-consequence relationship, indicating a performance coherent with the analysis of the behavior. Finally, results indicated that the clients' problems did not seem lead to significant differences in terms of the therapists' verbal behavior